A slight bending of an α-helix in FliM creates a counterclockwise-locked structure of the flagellar motor in Vibrio. (18th June 2021) - Takekawa, Norihiro; Nishikino, Tatsuro; Yamashita, Toshiki; Hori, Kiyoshiro; Onoue, Yasuhiro; Ihara, Kunio; Kojima, Seiji; Homma, Michio; Imada, Katsumi
Abstract: Many bacteria swim by rotating flagella. The chemotaxis system controls the direction of flagellar rotation. Vibrio alginolyticus, which has a single polar flagellum, swims smoothly by rotating the flagellar motor counterclockwise (CCW) in response to attractants. In response to repellents, the motor frequently switches its rotational direction between CCW and clockwise (CW). We isolated a mutant strain that swims with a CW-locked rotation of the flagellum, which pulls rather than pushes the cell. This CW phenotype arises from a R49P substitution in FliM, which is the component in the C-ring of the motor that binds the chemotaxis signalling protein, phosphorylated CheY. However, this phenotype is independent of CheY, indicating that the mutation produces a CW conformation of the C-ring in the absence of CheY. The crystal structure of FliM with the R49P substitution showed a conformational change in the N-terminal α-helix of the middle domain of FliM (FliMM ). This helix should mediates FliM–FliM interaction. The structural models of wild type and mutant C-ring showed that the relatively small conformational change in FliMM induces a drastic rearrangement of the conformation of the FliMM domain that generates a CW conformation of the C-ring.